Hares and rabbits (Leporidae) in collection of the Saris Museum, Bardejov (Slovakia) - Alexander Csanady (Theriologia Ukrainica, 2020)
The Natural History Department of the Saris Museum, Bardejov, Slovakia, was established in 1956 by PhMr. Tibor Weisz. The mammal collection consists of more than 5 000 specimens of 67 mammal species of the Slovakian fauna. The museum mostly represents the fauna of north-eastern Slovakia, i.e. the transition area between the Eastern and Western Carpathians and adjacent to the northernmost part of the Pannonian Basin. In the paper, data are presented on hare and rabbit specimens deposited in the collection of the Saris Museum in Bardejov (SMB), Slovakia. In total, data were evaluated on 27 specimens of the brown hare (Lepus europaeus) from twelve sites of Slovakia (n = 19), one site of Czech Silesia (n = 1), and from unknow localities (n = 7). Individuals were acquired in 1958–1971, but mainly in 1965–1966 (n = 19, 70.4 %). Among them, one specimen had signs of „albinism“ and was collected from Zlate village. The collection also includes a skull of a brown hare with anomalous dentition. Similarly, two skulls of the mountain hare (Lepus timidus) obtained from the Danish preparator N. H. Gustaffson were evaluated. Three rabit specimens were also found in the collection, including two skulls of the wild rabbit (Oryctolagus cuniculus) and a skin-mount and skull of a domestic rabbit (Oryctolagus cuniculus forma domestica). The collection contains 20 adult specimens (15 males and 5 females) with body size values recorded in the protocol cards. Mammalogical collections in the Saris Museum in Bardejov represent an outstanding scientific time capsule. All stored specimens in this particular and other similar collections, including those in local museums, will largely be needed and used as datasets by ecologists and conservationists in the future. It is necesary to preserve the collections, to computerise and digitise their inventories and the wealth of information they represent. At present, most of these data are not accessible electronically or online. Therefore, such collections, including that in Bardejov, must be sustained for a long term, which will require increased funding for their physical and scientific preservation.